EVALUATION OF BIO-EFFICACY OF NEWER MOLECULES OF INSECTICIDES AGAINST THRIPS, Megalurothrips usitatus IN YARD LONG BEAN, VIGNA UNGUICULATA SUBSP. SESQUIPEDALIS - RAMESH. M. MARADI; K. RAJASHEKHARAPPA; KIRANAMAYA PRADHAN (The Bioscan, 2020)
The present studies were conducted to test the efficacy of different insecticides viz., Acetamiprid, Imidacloprid, Chlorfenapyr, Diafenthiuron, Spiromesifen, Fenazaquin, Azadirachtin and Acephate against thrips under natural field condition during 2018-2019 at Agricultural and Horticultural Research Station, Bhavikere, UAHS, Shivamogga, Karnataka. Yard long bean, Vigna unguiculata subsp. Sesquipedalis is infested with many sucking pest viz., aphids, jassids, bugs, thrips and mites. Among the different sucking pests reported on yard long bean, thrips are the major pest at the time of flowering, causing severe yield loss under field condition. Observations on the population counts of thrips were recorded one 1 DBS and 1, 3, 5 and 7 DAS on five randomly selected plants on three leaves from the top, middle and bottom in each plot. Among the insecticides tested, the highest per cent reduction of thrips was recorded in the treatments Imidacloprid (83.91 %) followed by, Acetamiprid (81.20 %), Acephate (73.44 %) and Diafenthiuron (69.18 %). However, the least per cent reduction of thrips population was observed in Azadirachtin (51.93 %) treated plot when compared to untreated control (Pooled). Thus, it is concluded that all the studied insecticides proved effective against the thrips but, the toxicity studies of the pesticides were observed from maximum to minimum in the following order, Imidacloprid > Acetamaprid > Acephate > Diafenthiuron > Spiromecifen > Fenazaquin > Chlorfenapyr > Azadirachtin.